REKONTRUKSI BATAS USIA PERKAWINAN PASCA PUTUSAN MK NO. 22/PUU-XV/2017 SEBAGAI PENGUAT BANGSA DI ERA INDUSTRI 4.0 - Zain, Muhammad Fuad; Ansori, Ansori (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2019)
The construction of the Islamic Jurisprudence School contained in the Compilation of Islamic Law, and the Marriage Law collides with the era, especially at the age of marriage. Post the Constitution Court Verdict Number 22/ PUU-XV/ 2017 requires the state to immediately revise where the ideal age limit for male and female marriages becomes 18 years or 19 years. On the other hand, there are still many marital dispensations caused by legitimate extramarital pregnancy. This is homework for the state. The term bā'ah or isṭiṭa’ah in fiqh must be by the era, especially in the era of Industry 4.0, where the country that cannot adapt will be increasingly left behind. The concept of seriousness in the theory of Uṣūl al-Fiqh must be developed by seeing living law in Indonesian society in the framework of family law reform in Indonesia to build humanity as a whole for the creation of a great nation as the ideals of the nation’s founding father without having to harm the essence of Syariah itself.